Fabric-Based Multiband Spike Antenna for Wearable Applications (International Journal of Food and Nutritional Sciences, 2021)
The research places particular emphasis on assessing the antenna's performance in both the S and L bands, shedding light on its versatility across various frequency ranges. To comprehensively evaluate the antenna's effectiveness, a combination of simulation and measurement techniques is employed, with meticulous documentation and presentation of the results throughout this study. It's worth highlighting that all antennas subjected to evaluation yield promising results, effectively meeting the practical demands of real-world applications. The fusion of innovative multiband spike antenna designs with the utilization of fabric substrates underscores their potential for seamless integration into wearable technology. This research significantly contributes to the advancement of wearable communication systems by offering antenna solutions that are versatile, efficient, and adaptable, thus catering to the evolving needs of this rapidly growing field.